z-2=49z

Simple and best practice solution for z-2=49z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z-2=49z equation:



z-2=49z
We move all terms to the left:
z-2-(49z)=0
We add all the numbers together, and all the variables
-48z-2=0
We move all terms containing z to the left, all other terms to the right
-48z=2
z=2/-48
z=-1/24

See similar equations:

| -18m(m+2)=0 | | 4a2-5=43 | | -18m(m+2=0 | | -8+21/4x=-7/8 | | -7/8(w-16=70 | | 9x²+18x+82=0 | | 3+6+x=0 | | 36+5x=100-3x¨ | | -5.1b=255.51 | | 3(4x+10)=2x-30 | | -8+51/4x=-7/8 | | 25=15+(1/5a) | | 156=6(3n+2) | | (3)/(4)y-(5)/(6)=(2)/(3)y | | (1,9);m=–3 | | -3=4x-3+5 | | 22x=x/15+740 | | 15=5+2b | | -6.2n=173.6 | | (1/4x)+17=x-4 | | 25=15+1/5a | | 2(x+3)=3x−7 | | 3j-8=4 | | -2=n/2+-4 | | 40P=L+4w | | -6p+2-7=9p+10 | | j/23=15 | | 8nn=10 | | T+49=4t+1 | | -8.1y=269.73 | | 2s+10–7s–8+3s=7 | | 2/3(m-12)=6 |

Equations solver categories